2018
DOI: 10.1016/j.jhep.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 7 agonist GS-9620 induces prolonged inhibition of HBV via a type I interferon-dependent mechanism

Abstract: GS-9620 is a drug currently being tested in clinical trials for the treatment of chronic hepatitis B virus (HBV) infection. GS-9620 has previously been shown to suppress HBV in various animal models, but the underlying antiviral mechanisms were not completely understood. In this study, we determined that GS-9620 does not directly activate antiviral pathways in human liver cells, but can induce prolonged suppression of HBV via induction of an antiviral cytokine called interferon. However, interferon did not des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 32 publications
1
74
0
Order By: Relevance
“…A recent study showed that GS-9620 could induce multiple HBV suppressive factors in human PBMCs, leading to prolonged type I IFN-associated HBV suppression in primary human hepatocytes (PHH) and HepaRG cells, as well as enhanced biosynthesis of immunoproteasome subunits and display of an immunodominant viral peptide in PHH with HBV-infection. The latter may promote T cell recognition and activation in the host and viral control, though GS-9620 itself could not reduce cccDNA levels in hepatocyte culture systems (68).…”
Section: Tlr Ligandsmentioning
confidence: 96%
“…A recent study showed that GS-9620 could induce multiple HBV suppressive factors in human PBMCs, leading to prolonged type I IFN-associated HBV suppression in primary human hepatocytes (PHH) and HepaRG cells, as well as enhanced biosynthesis of immunoproteasome subunits and display of an immunodominant viral peptide in PHH with HBV-infection. The latter may promote T cell recognition and activation in the host and viral control, though GS-9620 itself could not reduce cccDNA levels in hepatocyte culture systems (68).…”
Section: Tlr Ligandsmentioning
confidence: 96%
“…Phase II Dose-dependent pharmacodynamic induction of ISG15 and host NK and HBVspecific T cell responses but no HBsAg reduction in patients. (87,88) Lack of effect for cccDNA in vitro (126) TLR 7 agonist JNJ-4964 (Janssen) Preclinical Antiviral efficacy (HBV DNA, HBsAg, liver HBV DNA, HBV RNA) in a mouse model (127) TLR 7 agonist GS-9688 (Gilead) Phase I Induced IL-12 and IL-RA1 in humans. Short duration did not result in HBsAg decline (128) TLR 8 agonist…”
Section: Tlr 7 Agonistmentioning
confidence: 99%
“…As mentioned above, the TLR7 agonist GS-9620 also showed strong and sustained antiviral effects against WHV and HBV when it was administrated orally in the woodchuck [ 56 ] and chimpanzee models [ 20 ]. The antiviral activity of GS-9620 was mainly dependent on induction of IFNs from innate immune cells, such as monocytes, but not activation of the antiviral pathway in hepatocytes [ 80 ]. Moreover, the GS-9620 also showed the immune modulatory effect on an HBV-specific immune response by enhancing antigen presentation in hepatocytes [ 80 ].…”
Section: Potential Therapeutic Approaches For Eliminating Chronic mentioning
confidence: 99%